Enhanced Repair Effect of Toll-Like Receptor 4 Activation on Neurotmesis: Assessment Using MR Neurography - Li, H.J.; Zhang, X.; Zhang, F.; Wen, X.H.; Lu, L.J.; Shen, J. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Alternative use of molecular approaches is promising for improving nerve regeneration in surgical repair of neurotmesis. The purpose of this study was to determine the role of MR imaging in assessment of the enhanced nerve regeneration with toll-like receptor 4 signaling activation in surgical repair of neurotmesis. MATERIALS AND METHODS: Forty-eight healthy rats in which the sciatic nerve was surgically transected followed by immediate surgical coaptation received intraperitoneal injection of toll-like receptor 4 agonist lipopolysaccharide (n = 24, study group) or phosphate buffered saline (n = 24, control group) until postoperative day 7. Sequential T2 measurements and gadofluorine M-enhanced MR imaging and sciatic functional index were obtained over an 8-week follow-up period, with histologic assessments performed at regular intervals. T2 relaxation times and gadofluorine enhancement of the distal nerve stumps were measured and compared between nerves treated with lipopolysaccharide and those treated with phosphate buffered saline. RESULTS: Nerves treated with lipopolysaccharide injection achieved better functional recovery and showed more prominent gadofluorine enhancement and prolonged T2 values during the degenerative phase compared with nerves treated with phosphate buffered saline. T2 values in nerves treated with lipopolysaccharide showed a more rapid return to baseline level than did gadofluorine enhancement. Histology exhibited more macrophage recruitment, faster myelin debris clearance, and more pronounced nerve regeneration in nerves treated with toll-like receptor 4 activation. CONCLUSIONS: The enhanced nerve repair with toll-like receptor 4 activation in surgical repair of neurotmesis can be monitored by using gadofluorine M-enhanced MR imaging and T2 relaxation time measurements. T2 relaxation time seems more sensitive than gadofluorine M-enhanced MR imaging for detecting such improved nerve regeneration. LFBLuxol fast blueLPSlipopolysaccharidePBSphosphate buffered salineSFIsciatic functional indexSIsignal intensityTLRtoll-like receptor